(untitled) (Bangladesh Medical Journal, 2024)
The functional outcome of flexor tendon injury after repair depends on multiple factors. Postoperative rehabilitation protocol plays an important role after a good repair for better functional outcomes. The aim of this study is to compare the outcome between early active mobilizations versus late mobilizations after flexor tendon repair in zone-II of hand. This Quasi-experimental (Nonrandomized control trial) was conducted from July 2018 to June 2021. Total 30 patients of flexor tendon injury in Zone-II of hand presented within 3 weeks were divided into two equal groups according to envelope technique, late mobilization (No intervention group) group- A and early active mobilization (Intervention group) group-B. All the flexor tendons were repaired with polypropylene 4/0 double strand score sutures and 6/0 epitendinous continuous sutures. In group-A mobilization started after 3 weeks and in group–B, intervention was given by active mobilization which was started at the day of operation. Buck Gramcko functional criteria and Louisville system were used for assessment of final result after 6 months of surgery. Male was predominant, M: F ratio was 3.3:1. Mean age of the respondent was 32.53±9.86 years. Dominant (Right) hand involvement was 70%. Student and service holder were the common involved group. Nearly three fourth (73%) of them had sharp cutting injury. More than half (53.10%) of the injuries were found in ring and little fingers followed by index (20.30%), middle (20.30%) and thumb (6.30%). Mean time interval between injury and operation was 11 days. Adhesion formation was the commonest complication that was 40% in group A and 20% in group B. More satisfactory outcome (87.50%) was found in group- B (Intervention group), that is patients who received early active mobilization; where the level of satisfactory outcome was less (62.50%) in group-A (Non-intervention group), that is patients who received late mobilization (p-value was significant <0.05). Early active mobilization following repair of flexor tendon in zone II of hand ensures better functional outcome with minimum complication compared to late mobilization. Bangladesh Med J. 2022 Sept; 51(3): 28-36